Atypical Clinical Presentation of Isolated Extraocular Muscle Sarcoid - Wing Lung Alvin So; Thomas G. Hardy; Penelope McKelvie (Case Reports in Ophthalmological Medicine)
A case of painless isolated extraocular muscle sarcoid and a literature review are presented. The atypical features in our case include a lack of overt inflammatory symptoms and signs, such as pain, ptosis, and diplopia. The presentation of minimal symptoms without improvement warrant a biopsy to establish the diagnosis and to administer appropriate treatment in order to prevent potential long-term complications from sarcoidosis.